A three-year experience with the balloon expandable GORE VIABAHN VBX in the treatment of thoraco-abdominal aortic aneurysms within the EXPAND trial - Usai, Marco Virgilio; Gargiulo, Mauro; Haulon, Stéphan; Tielliu, Ignace; Böckler, Dittmar; Verhagen, Hence; Fernández, Alba Méndez; Austermann, Martin Josef (Journal of vascular surgery, 2024)
Objective - The EXPAND registry is a post-market, multicenter registry that aims at evaluating the safety and performance of the GORE VIABAHN VBX balloon expandable endoprosthesis (VBX stent) implanted in peripheral vessels. This subgroup analysis assesses the 3-year outcomes of the VBX stent as a bridging stent graft for visceral vessels during branched endovascular aortic repair. - Methods - This prospective, multicenter, observational registry includes 16 European sites. Patients were enrolled from November 2018 to March 2022. Endpoints included 3-year primary patency (PP), secondary patency (SP), and stent graft-related death and serious adverse events. - Results - Seventy-three patients, of whom 57 (78.1%) were male, with a mean age of 73 years (±8.1 years) were included. At 3 years, 42 patients (57.5%) returned for follow-up. Overall, 223 target vessels (TVs) were treated. The estimated freedom from loss of TV PP was 93.6%. Per TV PP rates were 97.0% for the celiac trunk, 93.9% for the superior mesenteric artery, 91.2% for the left renal artery, and 92.5% for the right renal artery. The overall estimated freedom from loss of SP was 96.8%, and freedom from TV instability was 94.5%. - Conclusions - The VBX stent demonstrated excellent sustained results at 3 years with almost 94% PP, 97% SP, and 94.5% freedom from TV instability. Patency in the renal arteries was lower than in the celiac trunk and superior mesenteric artery. The VBX stent appears to be a reliable bridging stent for target vessels in branched endovascular aortic repair.